Ethylenediamine derivatives efficiently react with oxidized RNA 3′ ends providing access to mono and dually labelled RNA probes for enzymatic assays and in vivo translation. Issue 1 (30th September 2021) - Mamot, Adam; Sikorski, Pawel J; Siekierska, Aleksandra; de Witte, Peter; Kowalska, Joanna; Jemielity, Jacek
Abstract: Development of RNA-based technologies relies on the ability to detect, manipulate, and modify RNA. Efficient, selective and scalable covalent modification of long RNA molecules remains a challenge. We report a chemical method for modification of RNA 3′-end based on previously unrecognized superior reactivity of N -substituted ethylenediamines in reductive amination of periodate-oxidized RNA. Using this method, we obtained fluorescently labelled or biotinylated RNAs varying in length (from 3 to 2000 nt) and carrying different 5′ ends (including m 7 G cap) in high yields (70–100% by HPLC). The method is scalable (up to sub-milligrams of mRNA) and combined with label-facilitated HPLC purification yields highly homogeneous products. The combination of 3′-end labelling with 5′-end labelling by strain-promoted azide-alkyne cycloaddition (SPAAC) afforded a one-pot protocol for site-specific RNA bifunctionalization, providing access to two-colour fluorescent RNA probes. These probes exhibited fluorescence resonance energy transfer (FRET), which enabled real-time monitoring of several RNA hydrolase activities (RNase A, RNase T1, RNase R, Dcp1/2, and RNase H). Dually labelled mRNAs were efficiently translated in cultured cells and in zebrafish embryos, which combined with their detectability by fluorescent methods and scalability of the synthesis, opens new avenues for the investigation of mRNA metabolism and the fate of mRNA-based therapeutics.